2005
DOI: 10.1159/000086441
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin for the Symptomatic Treatment of Chronic Neuropathic Pain in Patients with Late-Stage Lyme Borreliosis: A Pilot Study

Abstract: Background: Chronic neuropathic pain occurs in 10–15% of patients with neuroborreliosis and is difficult to treat. Objective: We evaluated the effect of gabapentin monotherapy on residual pain in patients with neuroborreliosis after intravenous ceftriaxone treatment. Methods: Ten patients with neuroborreliosis and a long-lasting history of neurologic symptoms were treated with gabapentin, starting with 300 mg/day. Doses were raised over a period of 4–12 weeks to the individually effective and tolerated maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…But what about the late complaints that we want to treat? Klempner et al[ 31] showed that frequency and type of complaints reported by patients after EM are indistinguishable from those occurring in healthy individuals, and these complaints need a different type of treatment [35]. A 3-month course of antimicrobials (1 month of ceftriaxone followed by 2 months of doxycycline) was no more effective than placebo in alleviating symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…But what about the late complaints that we want to treat? Klempner et al[ 31] showed that frequency and type of complaints reported by patients after EM are indistinguishable from those occurring in healthy individuals, and these complaints need a different type of treatment [35]. A 3-month course of antimicrobials (1 month of ceftriaxone followed by 2 months of doxycycline) was no more effective than placebo in alleviating symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, gabapentin has been reported to be effective in the following pain status, including reflex sympathetic dystrophy (33), trigeminal neuralgia (34), postherpetic neuralgia (35,36), diabetic neuropathy (36,37), migraine (38), acute pain in herpes zoster infection (39), and other neuropathic pain status (40,41) (Table 2). Gabapentin is also effective in the postoperative pain management in different surgeries such as breast (42,43), hysterectomy (44,45), cholecystectomy (46), spinal (47), and knee (48) surgeries (Table 2).…”
Section: -2 Clinical Studiesmentioning
confidence: 99%
“…These include antidepressants, pregabalin and gabapentin, analgesics, biofeedback and complementary and alternative medicine. To date, the only published study is a small open-label trial that found that gabapentin reduced pain in 9/10 and improved quality of life in 5/10 patients with chronic post-Lyme neuropathic pain [124]. Until the medical community has better explanations and therapies for the millions who suffer unexplained chronic symptoms, some patients looking for answers will still come to blame Lyme disease for their illness.…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%